Structural, optical and electrical properties of fluorine doped tin oxide thin films deposited using inkjet printing technique - Wan Zurina Samad,; Muhamad Mat Salleh,; Ashkan Shafiee,; Mohd Ambar Yarmo, (Universiti Kebangsaan Malaysia, 2011)
This paper reports on structural, optical transmittance and electrical properties of fluorine-doped tin oxide (FTO) thin films deposited using an inkjet printer. The FTO ink was synthesized from a mixture of tin chloride pentahydrate (SnCl4.5H2O) and ammonium fluoride (NH4F) solutions. The thin films were deposited on glass substrates at ambient temperature or heated at 40oC and 60oC. The surface electronic state and the elemental composition of the thin films were analyzed using XPS spectroscopy. The spectra of the FTO thin films revealed that tin, oxygen, fluoride and carbon were present in the samples. The signals corresponding to Sn 3d5/2, O1s, and F1s were found at 486.6 eV, 530.5 eV and 684.5 eV, respectively. XRD analysis showed that the FTO films were in the form of crystalline with cassiterite shape. The optical and electrical properties of the films were affected by the deposition temperatures. It was observed the film deposited at 40oC has the optimum optical transmittance and sheet resistivity which were 91%T and 16 Ω/, respectively.